The Moderating Effect of Technology Attitude on the Relationship between Math Self-Efficacy and Attitudes towards Mathematics (Unnes Journal of Mathematics Education, 2023)
The study examined whether math self-efficacy significantly affects attitudes towards mathematics. It also explored the moderating effect of technology attitude on the link between mathematics self-efficacy and attitudes towards mathematics. A total of 174 Science, Technology and Engineering (STE) students (79 males and 95 females) of Tagum City National High School participated in the study. Three (3) valid and reliable instruments were used to assess students’ level of math self-efficacy, technology attitude, and attitudes towards mathematics. Results show that the level of math self-efficacy, and attitudes towards math of the STE students is moderate. Moreover, the level of technology attitude of the students is high. There is a significant relationship between math self-efficacy and attitudes towards math. However, there is no significant relationship between technology attitude and attitudes towards mathematics. The negative moderating effect of technology attitude on the relationship between math self-efficacy and attitudes towards math is established.